2023
DOI: 10.1108/jfmm-02-2022-0029
|View full text |Cite
|
Sign up to set email alerts
|

Social media fashion influencer eWOM communications: understanding the trajectory of sustainable fashion conversations on YouTube fashion haul videos

Abstract: PurposeThis study aims to examine YouTube comments relevant to sustainable fashion posted on fashion haul videos over the past decade (2011–2021). It is guided by two research questions: (1) How have sustainable fashion-related comments posted on YouTube fashion haul videos changed over time? and (2) What themes are relevant to sustainable fashion in the comments posted on fashion haul videos?Design/methodology/approachA data set of comments from 110 fashion haul videos posted on YouTube was refined to only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…As noted above, research examining demographics and psychographics are inconclusive on the variables that make ethical consumption more likely. Although interest in sustainable fashion has increased [14,19,20,24], it is insignificant when compared to the DSP of the fast fashion industry [3,4]. As the main consumers of fast fashion, Generation Z are also the focus of fast fashion marketing and more responsive to the tactics [13].…”
Section: Social Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…As noted above, research examining demographics and psychographics are inconclusive on the variables that make ethical consumption more likely. Although interest in sustainable fashion has increased [14,19,20,24], it is insignificant when compared to the DSP of the fast fashion industry [3,4]. As the main consumers of fast fashion, Generation Z are also the focus of fast fashion marketing and more responsive to the tactics [13].…”
Section: Social Contextmentioning
confidence: 99%
“…Further stimulation of the frequent impulsive fashion consumption process is found in the hedonic emotive response that fashion acquisition provides. For example, Ritch et al [13] found that consumers experience excitement when waiting for their purchase to arrive, and this unwrapping is often captured on social media for entertainment [24]. Engaging on social media is often a passive act, prompted by marketing that draws the consumer into social media, where consumption is just a few clicks away [8].…”
Section: Emotional Capital Of Fashion Engagementmentioning
confidence: 99%
See 3 more Smart Citations